Kesulitan Belajar Siswa Dalam Pembelajaran Bahasa Jepang Kelas XI Bahasa SMA Negeri 2 Singaraja Tahun Ajaran 2022/2023 - Luh Gede Fitria Budiani; Putu Dewi Merlyna Yuda Pramesti; I Kadek Antartika (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to analyze students' learning difficulties in learning Japanese in class XI Language SMA Negeri 2 Singaraja in terms of internal and external factors. The method used is descriptive quantitative method. The population in this study amounted to 68 students of class XI Language. The sample in this study was 59 students of class XI Language. The data collection instrument is a questionnaire. The results showed that there were learning difficulties experienced by students of class XI Language in terms of internal factors and external factors. On the internal factor of the motivational aspect with a percentage value of 61%, on the interest aspect with a percentage value of 56%, and on the attitude aspect with a percentage value of 57%, which means that the three values ​​are in the unfavorable criteria. The external factor is the learning difficulties of class XI language students in terms of the school environment with a percentage value of 59%, which means that the indicators on aspects of the school environment are in the unfavorable criteria. But there are no difficulties in aspects of the family environment. Therefore, it can be concluded that there are students' learning difficulties in learning Japanese in class XI Language in terms of internal factors and external factors.